2020
DOI: 10.1136/annrheumdis-2020-eular.2753
|View full text |Cite
|
Sign up to set email alerts
|

Ab1216 interstitial Pneumonia With Autoimmune Features (Ipaf): A Single Center, Prospective Study

Abstract: Background:Interstitial pneumonia with autoimmune features (IPAF)1describes a group of patients with interstitial lung disease and autoimmune features who do not meet the classification criteria for a specific connective tissue disease. Limited data regarding IPAF are available so far.Objectives:To identify the epidemiological and clinical characteristics of patients with IPAF and to observe disease progression, response to treatment and frequency of infections in 1-year follow-up period.Methods:Thirty-nine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Juhsz et al reviewed the clinical microbiological characteristics of bacteria, especially their role in lower respiratory tract infections and antibiotic treatment selection [ 4 ]. Karampeli et al understood the epidemiological and clinical characteristics of patients with interstitial pneumonia with autoimmune features and observed disease progression, treatment response, and infection frequency during a 1-year follow-up period [ 5 ]. Gugu et al identified the combined effect of snail mucin as a natural product antibacterial agent of animal origin and lincomycin against different strains of Streptococcus pneumoniae [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Juhsz et al reviewed the clinical microbiological characteristics of bacteria, especially their role in lower respiratory tract infections and antibiotic treatment selection [ 4 ]. Karampeli et al understood the epidemiological and clinical characteristics of patients with interstitial pneumonia with autoimmune features and observed disease progression, treatment response, and infection frequency during a 1-year follow-up period [ 5 ]. Gugu et al identified the combined effect of snail mucin as a natural product antibacterial agent of animal origin and lincomycin against different strains of Streptococcus pneumoniae [ 6 ].…”
Section: Introductionmentioning
confidence: 99%